Boosting photo charge carrier transport properties of perovskite BaSnO3 photoanodes by Sr doping for enhanced DSSCs performance. (10th February 2019) - Rajamanickam, N.; Soundarrajan, P.; Senthil Kumar, S.M.; Jayakumar, K.; Ramachandran, K.
Abstract: BaSnO3 (BSO) could be becoming an important next generation electron transport material in semiconductor technology due to its abnormal electrical properties even at room temperature. In this study, the strontium (Sr) is doped into BSO semiconductor via the facile co-precipitation method and then used as electron transporter in dye sensitized solar cells (DSSCs) is reported towards improving the power conversion efficiency (PCE). The physiochemical properties changes in the BSO systems by Sr doping assisted for an expeditious photo charge carrier transportation by making a desirable conduction band edge alignment with neighbouring TiO2 layer when use in BSO/TiCl4 treatment/TiCl4 scattering layer based photoanodes is confirmed by impedance studies. So, our new photoelectrode composition, 5% Sr: BSO/1 min TiCl4 treatment/TiO2 scattering layer yields one of the highest PCE by the outcome of 16.95 mA cm −2 ( J sc ), 0.63 (FF), and 0.82 V ( V oc ), which is 8.83%. This result shows superior PCE among all our early reports of photoanodes such as BSO, BSO/scattering layer, BSO/TiCl4 treatment, BSO/TiCl4 treatment/scattering layer and 3% Fe: BSO/TiCl4 treatment/scattering layer. On the basis of recent reports, a gradual upsurge in the efficiency of BSO nanostructures based photoanodes under easily reproducible scientific/rational approach will facilitate an astonishing possibility to enhancing the PCE which confidently reinforce the probability of implementation in practical life and is indispensable for balancing the future non-renewable energy dearth. Graphical abstract: Image 1